Preparatory living lab workshops under the IntelComp platform: An enabler of the solution for sustainability challenges of climate change in Greece - Papadaki, Lydia; Stavridis, Charalampos; Koundouri, Phoebe; Grypari, Ioanna; Kazbek, Madina; Papageorgiou, Haris; Theodossiou, Nicolaos (Frontiers in Environmental Economics, 2023)
The phenomena of climate change transcend all national and regional boundaries. Human health, agriculture and food production, forest fires, changes in ocean salinity, and other human and environmental phenomena are only a few examples of how it affects both. To address this complex challenge, we must determine the areas of the country of interest, in this case, Greece, that have been most adversely affected by climate. Greece is surrounded by water, and a significant part of its GDP is derived from the marine and maritime industries, including tourism. These industries are particularly vulnerable to the effects of the climate crisis, from rising sea levels and water acidification to declining fish stocks and biodiversity loss. Since the start of the IntelComp project, a Preparatory Living Lab (PLL) has been planned and delivered, feeding into the development of the IntelComp platform and the Living Lab on Climate Change Adaptation. The PLL led to the identification of the needs and gaps in the Mediterranean and its surrounding seas and the selection of the Energy Sector as the primary focus sector for the Climate Change case study of the IntelComp project.